A bibliometric analysis of the 50 most cited papers in cleft lip and palate. Issue 1 (February 2015) - Mahon, Nicola A.; Joyce, Cormac W.
Abstract Citation analysis is an established bibliometric method which catalogues papers according to the number of times they have been referenced. It is believed that the total number of citations an article receives reflects its importance among its peers. Never before has a bibliometric analysis been performed in the area of Cleft Lip and Palate. Our citation analysis creates a comprehensive list of the 50 most influential papers in this field. Journals specializing in Cleft Palate, Craniofacial, Plastic Surgery, Maxillofacial Surgery, Aesthetics and Radiology were searched to establish which articles most enriched the specialty over the past 70 years. The results show an interesting collection of papers which reveal developing trends in surgical techniques. These landmark papers mould and influence management and decision-making today.